Data mining techniques for disease risk prediction model: A systematic literature review - Ahmad W.M.T.W.; Ghani N.L.A.; Drus S.M. (Springer Verlag, 2023)
Decision making; Decision trees; Forecasting; Health care; Soft computing; Accuracy evaluation; Classification technique; Data mining algorithm; Descriptive analysis; Disease risks; Infectious disease; Risk prediction models; Systematic literature review; Data mining